Regulation of the Central Carbon Metabolism in Apple Fruit Exposed to Postharvest Low-Oxygen Stress - Boeckx, Jelena; Pols, Suzane; Hertog, Maarten L. A. T. M.; Nicolaï, Bart M. (Frontiers in Plant Science, 2019)
After harvest, fruit remain metabolically active and continue to ripen. The main goal of postharvest storage is to slow down the metabolic activity of the detached fruit. In many cases, this is accomplished by storing fruit at low temperature in combination with low oxygen (O2) and high carbon dioxide (CO2) partial pressures. However, altering the normal atmospheric conditions is not without any risk and can induce low-O2 stress. This review focuses on the central carbon metabolism of apple fruit during postharvest storage, both under normal O2 conditions and under low-O2 stress conditions. While the current review is focused on apple fruit, most research on the central carbon metabolism, low-O2 stress, and O2 sensing has been done on a range of different model plants (e.g., Arabidopsis, potato, rice, and maize) using various plant organs (e.g., seedlings, tubers, roots, and leaves). This review pulls together this information from the various sources into a coherent overview to facilitate the research on the central carbon metabolism in apple fruit exposed to postharvest low-O2 stress.